Shocks, assets and social protection: a gendered analysis of Ecuador, Ghana and Karnataka, India - Doss, Cheryl (2015)
This study explores the shocks experienced by households and the coping strategies employed by them. Women and men living in the same household may not always experience shocks or be impacted by them in the same way. The coping strategies employed depend on the nature of the shock, who experiences the shock and the resources that are available to respond to the shock. Women and men do not always have access to the same pool of resources and may therefore employ different coping strategies even when experiencing the same shock. Different coping strategies can have different welfare implications in the long term.